Effects of tapering on performance in endurance athletes: A systematic review and meta-analysis - Wang, Z.; Wang, Y. T.; Gao, W.; Zhong, Y. (PLOS ONE, 2023)
Objective: To assess the responses to taper in endurance athletes using meta-analysis.